Development of Odonata as A Nature Tourism Product for Peat Swamp Ecosystem in North Ayer Hitam Forest Reserve, Johor - Binti Muazam, Fatin Nur Izzati; Binti Mohamed , Maryati; Bin Zakaria, Mohammad Zulhusni; Cuevas Linatoc, Alona (Journal of Sustainable Natural Resources, 2023)
Odonates are water quality indicator for the health of freshwater ecosystem, had been used in pharmacology, as dietary items, predators and controlling human diseases. Odonata have a strong tradition of being involved in relaxation and recreation activities in various Asian nations, such as China and Japan. A study on odonate as tourism product was carried out at North Ayer Hitam Forest Reserve, Johor for eight days. The study firstly aimed to determine the diversity of odonate on site. Ten flagships species was then selected based on criteria of a good nature tourism product. The research continued to develop odonatourism as a new product in North Ayer Hitam Forest Reserve, Johor. The method used for species inventory were sticky trapping, sweep netting, and point-counting survey. A total number of 35 species with 465 individuals - had been collected during the research. Data collected revealed that the diversity of odonate in the sampling region is medium as evidenced by the Shannon Weiner Species Diversity Index (2.6126). Analyzing the 35 species of odonates, gauging against the eight Criteria of a Good Nature Tourism Product, 10 species indicated having potentials to be developed into nature tourism products.  Based on the selected 10 flagship species, a promotional brochure and a prototype of souvenir were created. Although this research mainly dealt with promoting odonate as potential nature tourism products the necessity to maintain North Ayer Hitam Forest Reserve in Johor is also highlighted.